What's the Story?: Exploring Parent–Teacher Communication through ePortfolios. Issue 4 (December 2017) - Higgins, Amanda; Cherrington, Sue
ELECTRONIC PORTFOLIOS (ePORTFOLIOS) ARE a relatively new phenomenon in early childhood education (ECE) with minimal existing research available on their use and effectiveness as a learning and communication tool in ECE. This article reports on a study examining the influence of ePortfolios on parent–teacher communication in one early childhood (EC) service. Reported data has been drawn from online surveys, document analysis of ePortfolios, individual interviews and focus group interviews with parents and teachers. Thematic analysis identified two main themes: the benefits and drawbacks of communicating via the ePortfolio, and the types of communication that were evident.